Why bank money creation? - Hans Gersbach; Sebastian Zelzner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2022)
We provide a rationale for bank money creation in our current monetary system by investigating its merits over a system with banks as intermediaries of loanable funds. The latter system could result when CBDCs are introduced. In the loanable funds system, households limit banks' leverage ratios when providing deposits to make sure they have enough "skin in the game" to opt for loan monitoring. When there is unobservable heterogeneity among banks with regard to their (opportunity) costs from monitoring, aggregate lending to bank-dependent firms is inefficiently low. A monetary system with bank money creation alleviates this problem, as banks can initiate lending by creating bank deposits without relying on household funding. With a suitable regulatory leverage constraint, the gains from higher lending by banks with a high repayment pledgeability outweigh losses from banks which are less diligent in monitoring. Bank-risk assessments, combined with appropriate risksensitive capital requirements, can reduce or even eliminate such losses.
urn:nbn:de:hebis:30:3-634174
Keywords: E42; E44; E51; G21; G28; 330; monetary system; banking; money creation; loanable funds; capitalrequirements; leverage constraint; asymmetric information; moral hazard; CBDC